Generalized discrete fourier transform based improvement of partial transmit sequence scheme to reduce PAPR in OFDM systems - Elshirkasi, Ahmed Mohamed; Siddiqi, Mohammad Umar; Habaebi, Mohamed Hadi (Little Lion Scientific Islamabad Pakistan, 2015)
Future applications of communication systems require higher data rates and more mobility. Orthogonal frequency division multiplexing (OFDM) can achieve these goals due to it is ability to reach high bit rates over fading channels as well as its efficient utilization of the bandwidth. However, the transmitted signal of OFDM suffers from high peak to average power ratio (PAPR). Such signals require high power amplifier (HPA) of large dynamic range to amplify the whole transmitted signal without distorting it. This paper gives the results of a study on the effect of applying the nonlinear phase of generalized discrete Fourier transform (GDFT) theory on the performance of partial transmit sequence (PTS) which is one of proposed techniques to mitigate high PAPR of OFDM signal. This has been done by modifying the phase of data symbols in each OFDM block before PTS is applied. Simulation results show that the proposed scheme requires half the number of sub-blocks to achieve the same amount of PAPR reduction compared with the original PTS scheme.